Assessing the possibilities of CNT and EFB fiber reinforcement in rammed earth nanocomposites for structural stability enhancement - Wijaya, Kinanti; Siregar, Syafiatun; Sutrisno, Sutrisno; Idris, Iswandi (Eastern-European Journal of Enterprise Technologies, 2025)
The object of the study is the rammed earth nanocomposites. Rammed earth nanocomposites reinforced with carbon nanotubes (CNT) and oil palm empty bunch (EFB) fibers provide nanoscale cohesion, and EFB fibers offer macroscale crack bridging, this research aims to significantly improve the material’s mechanical performance. This study pioneers a nanocomposite approach by integrating 1-2 % CNT and EFB fibers into rammed earth, achieving a 539 % increase in compressive strength (from 1.43 MPa to 9.13 MPa) and 34.671 kN buckling resistance to improve structural performance especially for the stability for sustainable construction applications. Standard rammed earth had a compressive strength of 1.43 MPa and buckling resistance, limiting its use; however, when 1 % CNT was added, increased compressive strength to 6.43 MPa (cube) and 6.58 MPa (cylinder), while 2 % CNT further enhanced it to 8.56 MPa and 9.13 MPa, respectively. Flexural strength also improved from 0.98 MPa to 3.60 MPa (beam). Cylindrical specimens showed optimal performance due to uniform stress distribution (34.671 kN buckling resistance). Microstructural analysis reveals CNT enhance nano-scale cohesion while EFB fibers provide macro-scale crack bridging. Compared to conventional concrete, the composite reduces embodied carbon by 62 % (per ISO 14040 LCA standards) and material density by 26 % (1.48 vs 2.0 g/cm3). These findings establish a new paradigm for sustainable seismic-resistant construction in developing tropical regions where both laterite soil and palm oil waste are abundant. The synergy of CNT (nanoscale cohesion) and EFB (load distribution) addresses key limitations. This material is suitable for eco-friendly construction, seismic-resistant structures, and lightweight partitions, offering a sustainable alternative to concrete/steel. The project simultaneously advances sustainable construction materials and provides a blueprint for vocational education that bridges technical and soft skills